Effect of CO2 on production of jatropha oil methyl ester via sub/supercritical methanol - Nur Adillah, Abdul Razak (2010)
This research focused on effect of co-solvent towards production of biodiesel via sub/supercritical methanol. The objective of this research is to study the effect of CO2 as co-solvent in production of Jatropha Oil Methyl Ester at sub/Supercritical of methanol and to optimize operating parameters such as reaction temperature, CO2 \v olume and the ratio of methanol/oil. The reaction has been carried out in the absence of catalyst due to the easier purification process. The raw materials used in this study are refined jatropha oil, high grade methanol (solvent) and CO (co-solvent). It is believed that addition of co-solvent with lower critical point will reduce the severity of reaction temperature and pressure. Jatropha oil, methanol and CO2 were charged into the supercritical reactor with appropriate mole ratio. The mixture is then heated up to desired reaction temperature. The reaction pressure was recorded and the reactor is cooling down until room temperature. The product is then removed and proceeds for purification. The product sample is analyzed to determine the yield percentage of methyl ester using gas chromatography. The duration for reaction was fixed at 5 minutes. The reaction temperature was varied at 160oC to 300oC. CO is added into reaction system and act as co-solvent in order to decrease the pressure. The amount of CO2added is measured in terms of volumes, which are at 0.018 m3, 0.055 m32 and 0.092 m3, respectively. Result shows that, addition of in the reaction system manage to decrease the reaction pressure. The best volume of CO2 addition obtained from this study was 0.018 m3with reaction pressure 15.1 MPa and yields 85.45 w/w% of jatropha oil methyl ester (JOME) at reaction temperature of 300oC. This study shows that, the addition of CO ]2as cosolvent is a promising method to reduce the reaction pressure and acceptable for future studies.